2018
DOI: 10.1080/09674845.2017.1402404
|View full text |Cite
|
Sign up to set email alerts
|

Potential value of circulating microRNA-126 and microRNA-210 as biomarkers for type 2 diabetes with coronary artery disease

Abstract: Plasma miR-126 and miR-210 levels may be biomarkers for diabetes with or without CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…Whether the detected miRNAs are specific of MPM or rather indicative of a disease status of the subjects remains an unsolved question. Just to make some examples, alteration of circulating miR-126 expression has been associated not only with MPM but also with other neoplastic conditions [e.g., NSCLC (96) or colorectal carcinoma (97)], and with non-neoplastic conditions such as diabetes (98); in addition, altered expression of circulating miR-103a-3p was associated also with prostate cancer (99).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Whether the detected miRNAs are specific of MPM or rather indicative of a disease status of the subjects remains an unsolved question. Just to make some examples, alteration of circulating miR-126 expression has been associated not only with MPM but also with other neoplastic conditions [e.g., NSCLC (96) or colorectal carcinoma (97)], and with non-neoplastic conditions such as diabetes (98); in addition, altered expression of circulating miR-103a-3p was associated also with prostate cancer (99).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Several environmental (obesity) and genetic factors (such as microRNAs) contribute to the multiple pathophysiological disturbances that are responsible for impaired glucose homeostasis in this disease. Amr and colleagues [13] hypothesised that plasma miR-126 and miR-210 are linked to coronary artery disease (CAD) in diabetes patients, recruiting 20 healthy volunteers and 100 patients with diabetes (54 patients without CAD and 46 patients with CAD). Plasma miR-126 and miR-210 (assessed by quantitative RT-PCR) were mean (SD) 0.38 (0.03) and 5.3 (0.56) in diabetes alone vs. 0.08 (0.03) and 21.44 (0.97) in diabetes with CAD, respectively (both P < 0.0001).…”
Section: Blood Sciencementioning
confidence: 99%
“…Pathogenesis is not well defined, but it is possible that genetic and environmental factors result in an aberrant immune response to a subset of commensal enteric bacteria. Hosseinpour et al [13] conducted a case-control study of 180 patients and 250 controls to evaluate variants in SNPs in genes for tumour suppressor protein p53 and miR-34b/c on the development of UC. They found that subjects with the p53 variant genotype (Pro/Pro) showed a significantly increased risk of UC relative to Arg/Arg carriers (Odds ratio 7.11, 95% CI 3.22-15.69; P < 0.001).…”
Section: Blood Sciencementioning
confidence: 99%
See 2 more Smart Citations